Pesticide residues in foods and the environment as a consequence of crop production - Tejada, A. W. (1995)
The residues of pesticides in rice paddy and its environment, in vegetables and other crops were determined.

In rice, the residues are seldom detected on the grains at harvest. However, treated paddy water drained in irrigation canals showed concentrations of pesticides ranging from 0.185 to 0.283 mg/L. 50 m from the treated paddy. The frogs were killed after one hour exposure to the canals. Traces of these pesticides were also detected in some tributaries of the river ranging from 0.04 to 0.08 ppb and down to Laguna Lake at 0.02 ppb. Similarly, some of the tributaries to the Manila Bay contained residues of DDT, DDE and DDD (0.2-2.0 ppb). Lakes Buhi and Bato have no pesticide contamination in fish, water nor sediments.

Most of the pesticides used in rice production were extremely toxic to Tilapia fish with LC,, ranging from 10 to 0.6 ppm. The real danger lies in the ability of these fish to bioconcentrate the residues, posing hazards to consumers. Even ducks collected within the vicinity of the treated field contained residues of these pesticides. Ra-diotracers were used to determine the movement of pesticides in the animal body. In fish, the residues were concen-trated in the intestines, then in the fillet and least in the head. In goat, 77% of the actual dose was excreted in the urine, 3% in the feces and 0.05% in the milk. The residues remaining in the body were concentrated in the fat (0.8 ppm) and liver (0.6 ppm).

Well water within the vicinity of the treated paddy fields were also contaminated with these pesticides during the wet season.

Chronic effects of pesticides are significantly related to workers' exposure to pesticides. Safe reentry of work-ers in the treated fields can be correlated with residues remaining in water, plants and in the atmosphere. A 3 to 5 day PHI may be recommended for safe reentry period in the field.

In vegetables, the farmers apply pesticides at least fifteen times per cropping season. A simple and rapid technique was developed to determine the residues of these pesticides. Out of 168 vegetable samples analyzed, 11% were positive of organophosphate and carbamate pesticides using rapid bioassay of pesticide residues (RBPR) while 3% were positive of organophosphates using the rapid field kit for organophosphates (RFKO). These simple tech-niques are 1000 times cheaper than the conventional technique. Confirmatory analysis by gas chromatography re-vealed that 3% contained residues exceeding the usual maximum residue limits set by FAO/WHO (0.2-0.5 mg/kg) for vegetables.

Washing and cooking rice and vegetables is highly recommended especially when these are treated at postharvest. Stored rice in pesticide treated sacks contained residues up to six months. These are considerably reduced (57-100%) if washed and cooked.

Tobacco also contained some chlorinated pesticides especially DDT since 1970 and although reduced in 1980, the levels were still beyond the MRL (1 mg/kg) set by Germany. Since then there has been no monitoring on tobacco.

Recently, infestation of coconut by mealy bugs lead researchers to inject pesticides on the trunk of trees. A similar study was conducted at the National Crop Protection Center, University of the Philippines Los Baños by root infusion of chlorpyrifos in coconut. The maximum uptake of the insecticide by the mature and young nuts occurred 13 to 15 days after root infusion and declined thereafter with residues remaining up to the 60th day at levels within the 2.0 mg/kg MRL set by FAO/WHO.

Some supervised residue data in different crops were generated to serve as basis for establishing MRL under local conditions. This is a good start because we are just basing our MRL on FAO/WHO recommendations which are mostly data from temperate countries where pest problems and pesticide management practices are different and where tolerances would likewise be different.
Keywords: Pesticide residues in food; Crop productions; Environmental health